Carbon‐Fiber Cloth Decorated with 3D Flower‐Like GO/WO3 Quantum Dots/TiO2 Microsphere with High Photocatalytic Activity under Natural Sunlight. (10th October 2021) - Wang, Chen; Wang, Shiliang; Qian, Guoping; Chen, Chuansheng
Abstract: Nanopowder photocatalyst suffers two serious problems (low photocatalytic efficiency, easy aggregation, and difficult recycling) in water treatment. For solving these issues, a 3D flower‐like graphene oxide (GO)/WO3 quantum dots (QDs)/TiO2 microsphere (FWGT) with excellent photocatalytic property is synthesized by a hydrothermal method which can degrade 100% Rhodamine B (RhB) within 10 min under solar light irradiation. Meanwhile, a carbon‐fiber cloth/FWGT (CF/FGT) membrane is constructed by decorating the FWGT microsphere on the surface of the carbon‐fiber cloth. CF/FGWT membrane displays better photocatalytic activity compared with carbon‐fiber cloth/flower‐like GO/TiO2 microsphere (CF/FGT) membrane, which the reaction rate constants of CF/FGWT membrane are 3.52 times higher than that of CF/FGT membrane. Moreover, the CF/FGWT membrane shows a little quality loss (about 1.7%) after several recycles, indicating the novel flexible photocatalytic membrane has great potential for purifying water. Abstract : The flower‐like graphene oxide (GO)/WO3 quantum dots (QDs)/TiO2 microsphere (FGWT), synthesized using a hydrothermal method, is successfully decorated on carbon fiber cloth, and a novel flexible photocatalytic membrane is obtained. Moreover, the photocatalytic property of the FGWT microsphere and flexible photocatalytic membrane is studied under natural sunlight.